1965
DOI: 10.1126/science.148.3678.1725
|View full text |Cite
|
Sign up to set email alerts
|

Microseisms from Hurricane "Hilda"

Abstract: As hurricane "Hilda" crossed the Gulf of Mexico the dominant period of the microseisms shifted from about 8 to 5 seconds as the eye reached water about 150 to 200 meters deep. The conversion of wind energy to microseismic energy is most efficient in water depths from 20 to 200 meters. There is no evidence that two periods, one twice the other, are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Observations have repeatedly indicated that large maritime storms produce microbaroms; however, the specifics of such generation is still a topic of some debate [ Banerji , ; Bremaecher , ; Hetzer et al , ; Stopa et al , , ]. It has been proposed by Hetzer et al [] that the interaction of the storm‐induced swell with the background swell can produce the counterpropagating waves required to generate microbaroms.…”
Section: Introductionmentioning
confidence: 99%
“…Observations have repeatedly indicated that large maritime storms produce microbaroms; however, the specifics of such generation is still a topic of some debate [ Banerji , ; Bremaecher , ; Hetzer et al , ; Stopa et al , , ]. It has been proposed by Hetzer et al [] that the interaction of the storm‐induced swell with the background swell can produce the counterpropagating waves required to generate microbaroms.…”
Section: Introductionmentioning
confidence: 99%